Heterogeneity Effect on Polymer Injection: a Study of Sumatra Light Oil - Romal Ramadhan; Adi Novriansyah; Tomi Erfando; Suparit Tangparitkul; Arik Daniati; Asep Kurnia Permadi; Muslim Abdurrahman (Scientific Contributions Oil and Gas, 2023)
The production of oil and gas is heavily dependent on the heterogeneity of the reservoir. Optimizing the production plan and maximizing recovery from the reservoir depends on an understanding of how heterogeneity affects fluid flow and recovery. Techniques such as water flooding and polymer flooding were used to increase oil production from reservoirs while evaluating the impact of reservoir heterogeneity. Numerical simulations in homogeneous and heterogeneous models were performed in this research to identify the optimal operational parameters that will optimize oil recovery and assess the effect of heterogeneity in the reservoir on the recovery factor of the reservoir. The result showed that the homogeneous model obtained 59.86% of the oil recovery factor, while the heterogeneous reservoirs for Lk = 0.2, 0.4, and 0.6 resulted from 45.83%, 69.27%, and 80.46% of oil recovery after twenty years of production, respectively. The heterogeneous reservoir with Lk = 0.6 indicated the highest sweep efficiency compared to other scenarios, while the reservoir with Lk = 0.2 showed the lowest sweep efficiency